(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2023)
E-letter is a web-based application used for correspondence activities which makes it easier to time-efficient company correspondence activities while triggering pros and cons among users in its implementation. The aim of this research is to identify E-letters taking place in company correspondence amidst the emergence of pros and cons between users while carrying out business correspondence giving rise to various meanings of E-letters which continue to persist in supporting the achievement of organizational goals. This research uses a qualitative approach with a case study method. The results of this research show that the use of e-letters in private universities gives rise to various different user perspectives, but the use of e-letters continues. The use of e-letters provides convenience and accuracy in correspondence starting from the creation and distribution of official letters to the process of information retrieval and storage. This system minimizes misuse of official documents because it has a security system where only registered employees can access the system.